Evaluation of the In Vitro Efficacy of Artemisia annua, Rumex abyssinicus, and Catha edulis Forsk Extracts in Cancer and Trypanosoma brucei Cells. (22nd September 2013) - Worku, Netsanet; Mossie, Andualem; Stich, August; Daugschies, Arwid; Trettner, Susanne; Hemdan, Nasr Y. A.; Birkenmeier, Gerd
Abstract : The current drugs against sleeping sickness are derived from cancer chemotherapeutic approaches. Herein, we aimed at evaluating the in vitro effect of alcoholic extracts of Artemisia annua (AMR), Rumex abyssinicus (RMA), and Catha edulis Forsk (CEF) on proliferation/viability of 1321N1 astrocytoma, MCF-7 breast cancer, THP-1 leukemia, and LNCaP, Du-145, and PC-3 prostate cancer cells and on Trypanosoma brucei cells. Proliferation of tumor cells was evaluated by WST-1 assay and viability/behaviour of T. brucei by cell counting and light microscopy. CEF was the most efficient growth inhibitor in comparison to AMR and RMA. Nevertheless, in LNCaP and THP-1 cells, all extracts significantly inhibited tumor growth at 3  μ g/mL. All extracts inhibited proliferation of T. brucei cells in a concentration-dependent manner. Microscopic analysis revealed that 95% of the T. brucei cells died when exposed to 33  μ g/mL CEF for 3 hrs. Similar results were obtained using 33  μ g/mL AMR for 6 hrs. In case of RMA, however, higher concentrations were necessary to obtain similar effects on T. brucei . This demonstrates the antitumor efficacy of these extracts as well as their ability to dampen viability and proliferation of T. brucei, suggesting a common mechanism of action on highly proliferative cells, most probably by targeting cell metabolism.